Probing the history of ultra‐high temperature metamorphism through rare earth element diffusion in zircon. (1st September 2021) - Blereau, Eleanore; Clark, Chris; Kinny, Peter D.; Sansom, Eleanor; Taylor, Richard J. M.; Hand, Martin
Abstract: The extent to which solid‐state volume diffusion modifies rare earth element (REE) abundances in accessory minerals during high‐temperature metamorphism governs our ability to link recorded trace‐element compositions to particular thermal events. We model diffusion of REE in zircon under different temperature–time conditions and show that, for both short‐lived (e.g. 1100°C for 1–5 Ma) and more prolonged (e.g. 1050°C for 10–30 Ma or 1000°C for 200 Ma) episodes of ultra‐high‐temperature (UHT) metamorphism, REE diffusion in igneous zircon is sufficiently rapid for REE in a ~50‐μm grain to equilibrate with the new metamorphic mineral assemblage of the host rock. By contrast, unless diffusion is accelerated by recrystallization, the presence of fluids or other processes at temperatures below 900°C zircon will largely retain its original pre‐metamorphic REE abundance pattern, even when the thermal event is long lived (≥100 Ma). Where volume diffusion is dominant, for instance, in the absence of a fluid phase, the sensitivity of REE mobility to temperature can help constrain the temperature–time path of high‐grade metamorphic rocks. Modelling of well‐characterized natural samples from the regional‐scale aureole surrounding the Rogaland Igneous Complex (RIC) in SW Norway shows that variations in REE concentration patterns in zircon indicate a T–t evolution that is consistent with independent P–T–t estimates for regional metamorphism based on phase equilibrium modelling (850–950°C at 7–8 kbar for ~100 Ma). Greater modification of REE abundance patterns in zircons within 2 km of the RIC contact, however, indicates that UHT conditions persisted for ~150 Ma close to the intrusion, with a temperature of ~1100°C for 1–5 Ma at the RIC contact. Thermal modelling suggests that the inferred T–t histories of samples from different distances from the RIC contact are best explained if the complex was emplaced incrementally over 1–5 Ma.